Verbotene Klänge Komponisten im Exil = Forbidden sounds : composers in exile - Krenek, Ernst 1900-1991; Zemlinsky, Alexander von 1871-1942; Schreker, Franz 1878-1934; Schulhoff, Erwin 1894-1942; Ullmann, Viktor 1898-1944; Hindemith, Paul 1895-1963; Schönberg, Arnold 1874-1951; Wellesz, Egon 1885-1974; Milhaud, Darius 1892-1974; Eisler, Hanns 1898-1962; Weill, Kurt 1900-1950; Dessau, Paul 1894-1979; et al. (Delta Music GmbH, 2004)
Documentary about the suppression of Jewish and modernist music in Nazi Germany. The film contains interviews with some musicians who were victoms of or witnesses to this persecution, including Ernst Krenek, Hans Ulrich Engelmann, Cora Schröder-Auerbach, Berthold Goldschmidt, Alfred Goodman, Alexander Ringer, Oskar Sala, and Herbert Zipper.
Bildformat: 4:3
Interpreten unter anderem: (Choreinstudierung). (Dirigent)
Aufnahme:
Keywords: Entartete Musik; Exil; Komponist; Film; DVD-Video